Public Library Interior Design with Biophilic Concept in Sleman Regency - vernanda salsabila zalfa; Lu’lu’ Purwaningrum (Faculty Of Arts and Design Sebelas Maret University, 2024)
The Sleman Regency Library is an educational facility established by the government to provide educational services and fulfill the government's responsibility to enlighten the nation. It also reflects the vision and mission of Sleman Regency, articulated through the Smart City concept, which aims to manage resources effectively and efficiently, maximize public services, and support sustainable development. However, the library in Sleman still requires design improvements, as it currently has a rigid design, with a need for better space planning, circulation, and additional facilities to meet visitor needs and enhance their comfort. The interior design is based on David K. Ballast’s 1992 design method. This public library design incorporates the Biophilic concept, which aims to enhance human well-being both physically and mentally while fostering a positive connection between people and nature. The goal of this interior design is to improve the quality of the library as an educational space, make it appealing to the community, and optimize space planning and facilities to better meet public needs.